Marriage, bequest, and assortative matching in rural Ethiopia - Fafchamps, Marcel; Quisumbing, Agnes R. (University of Chicago Press, 2005)
This article examines the determinants of human and physical capital at marriage. Using detailed data from rural Ethiopia, we find that assets brought to marriage are distributed in a highly unequal manner. For first unions, assets brought to marriage are positively associated with parents' wealth, indicating that a bequest motive affects assets at marriage. Parental wealth affects the inheritance of neither groom nor bride. Sibling competition from brothers affects grooms' inheritance, but sisters have no effect. The marriage market is a major conduit for rural and gender inequality, although avenues do exist for couples to accumulate wealth over their life cycle.